Peran Mata Kuliah Microteaching Dalam Mengembangkan Keterampilan Dasar Mengajar Mahasiswa Program Studi Pendidikan Sejarah STKIP Sinar Pancasila - Augusta De Jesus Magalhaes (Journal on Education, 2024)
Microteaching is one of the courses that must be programmed by all students in the history education study program, in the sixth semester as a prerequisite before students go to school to carry out practical field experiences. The micro teaching course is a very vital activity for every student at the Teaching Faculty, and fulfills the need to be able to position himself completely and professionally in the teaching field. The aim of this microteaching course is to train basic teaching skills and prepare students in the history education study program as prospective teachers to face full teaching work in the classroom by having the knowledge, skills, abilities and attitudes as professional teachers. The role of lecturers in microteaching courses and student activity in learning activities is very important. In Micro Teaching learning activities, there are 10 basic skills that are really needed by a prospective teacher, including, 1) skills to open learning, 2) skills to explain, 3) skills to provide variations, 4) skills to ask questions, 5) skills to guide group discussions, 6) skills in guiding group discussions, 6) small group and individual teaching skills, 7) class management skills, 8) reinforcement skills, 9) skills in using media or tools, and 10) skills in closing learning. This research uses a qualitative descriptive method, where the data obtained is processed in narrative form.